2018
DOI: 10.1016/j.immuni.2017.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Immune Response by the Aryl Hydrocarbon Receptor

Abstract: The aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor that is activated by small molecules provided by the diet, microorganisms, metabolism, and pollutants. AhR is expressed by a number of immune cells, and thus AhR signaling provides a molecular pathway that integrates the effects of the environment and metabolism on the immune response. Studies have shown that AhR signaling plays important roles in the immune system in health and disease. As its activity is regulated by small molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
614
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 712 publications
(620 citation statements)
references
References 221 publications
(303 reference statements)
2
614
0
4
Order By: Relevance
“…S1A) and did not recover until later time points in both types of macrophages. It has been suggested that ligandbound AhR immediately translocates into the nucleus, where it forms a complex with ARNT (21,22,32). An immunoblot assay of nuclear and cytosolic fractions clearly shows that IS stimulation led to rapid translocation of AhR into the nucleus within 5 min (Supplemental Fig.…”
Section: Is-induced Tnf-a Expression Is Regulated By Ahr-mediated Resmentioning
confidence: 92%
See 3 more Smart Citations
“…S1A) and did not recover until later time points in both types of macrophages. It has been suggested that ligandbound AhR immediately translocates into the nucleus, where it forms a complex with ARNT (21,22,32). An immunoblot assay of nuclear and cytosolic fractions clearly shows that IS stimulation led to rapid translocation of AhR into the nucleus within 5 min (Supplemental Fig.…”
Section: Is-induced Tnf-a Expression Is Regulated By Ahr-mediated Resmentioning
confidence: 92%
“…This complex binds an AhR-specific binding sequence [xenobiotic-responsive element (XRE) or dioxin-responsive element] present in the promoters of a wide variety of target genes. It has been demonstrated that AhR activation also initiates negative feedback loops that restrict AhR signaling via its time-dependent degradation by the 26S proteasome (21,22). In addition, AhR functions as a component of many signaling pathways through its interaction with other proteins independent of its ability to bind to DNA (18,23).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Increased IDO expression associates with tolerogenic pathways because of Trp depletion and has been associated with the formation of tolerogenic dendritic cells and induction of T regulatory (T reg ) cells 6, 7. Kynurenines are Trp metabolites that stimulate aryl hydrocarbon receptors and associated downstream immunoregulatory pathways 8, 9…”
Section: Introductionmentioning
confidence: 99%